PENGARUH PENGAKUAN, KOMPENSASI DAN POLA KOMUNIKASI TERHADAP KETERLIBATAN KARYAWAN PADA PT. EASTERN PEARLS FLOUR MILLS MAKASSAR - Mashur Razak; Bambang Suharnanto (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
The research aims to know and analyze: the influence of recognition, compensation and communication patterns partially or simultaneously and the most dominant variable to employee engagement at PT. Eastern Pearl Flour Mills Makassar. The research used a survey with a sample of 83 people from a population of 500 people using the Slovin formula. The results research indicated that: recognition, compensation and communication patterns had a positive and significant effect partially and cimultant to employee engagement at PT Eastern Pearl Flour Mills Makassar, and compensation most dominant variable to employee engagement at PT. Eastern Pearl Flour Mills Makassar.